Continuation of atezolizumab plus bevacizumab beyond initial progressive disease: clinical benefits in patients with unresectable hepatocellular carcinoma – a multicenter cohort study - Tabuchi, Takaya; Taniki, Nobuhito; Ojiro, Keisuke; Kasuga, Ryosuke; Nakadai, Yukie; Chu, Po-Sung; Usui, Shingo; Shiba, Shunsuke; Tahara, Toshiyuki; Komatsu, Hirokazu; Fujita, Yuriko; Kaneko, Fumihiko; et al. (Frontiers in Immunology, 2025)
BackgroundThe clinical significance of treatment beyond progression (TBP) with immune checkpoint inhibitor-based therapy in hepatocellular carcinoma (HCC) remains unclear. As atezolizumab plus bevacizumab has become a first-line therapy for advanced HCC, understanding the real-world outcomes of TBP is increasingly relevant.MethodsWe conducted a multicenter retrospective observational study involving 122 patients with unresectable HCC treated with atezolizumab plus bevacizumab across nine liver centers in Japan. Among patients who experienced radiologic progressive disease (PD), clinical outcomes were compared between those who continued treatment beyond progression (TBP group) and those who discontinued therapy. Overall survival (OS), tumor response, and subgroup analyses based on major vessel involvement (MVI) were evaluated.ResultsAmong patients with PD, the median OS was not reached in the TBP group, compared to 13.6 months in the non-TBP group (HR 2.04; 95% CI 1.02–4.07; p=0.0435). When stratified by MVI status, patients without MVI who received TBP had significantly longer OS (median not reached) than those who received palliative care (median 6.2 months; HR 11.2; 95% CI 3.89–32.5; p<0.001). Among patients with MVI, TBP did not confer an OS benefit over palliative care (median OS: 10.4 months vs. 7.4 months; HR 2.24; p=0.260), whereas switching to subsequent chemotherapy showed improved OS (median 23.1 months vs. 7.4 months; HR 7.33; 95% CI 1.44–37.3; p=0.0164). Multivariate analysis identified MVI as an independent negative prognostic factor (HR 5.17; 95% CI 1.34–20.0; p=0.0172), even after adjusting for AFP ratio at progression.ConclusionsThis multicenter study suggests that continuation of atezolizumab plus bevacizumab beyond radiologic progression may improve survival outcomes in selected patients with unresectable HCC, particularly those without major vessel involvement. These findings support the integration of TBP into personalized treatment strategies in advanced HCC.